“Pranala” Website Magazine Making in Collaboration with Ekspresi Suara Remaja - R. Godham Wishnu Perdana; M. Bayu Widagdo . (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Website magazine become one source of information in this digital age. Music becomes commodities social exchange of teenager and young adult, especially in Semarang. Teenager and young adult looking for music information on the website magazine to the needs of their social exchange. This final project is intended to create website magazine which presents information about local music of Semarang city. This final project is a journalism product based on the theory of online journalism from book by Asep Syamsul M. Romli (2012) called Online Journalism. “Pranala” also became one of local movement that supports local wisdom. From the results of this final project , it is known that the visitors of “Pranala” is reach the target. The website visitors are always new every day and “Pranala”s social media followers also help spreading articles. It’s a prove that website magazine which presents music information of Semarang is required by teenager and young adult of the city. From the results of this final project, it is known that music theme-website magazine having influence on social exchange of teenager and young adult. Music theme-website magazine also can be a promotional medium for musicians for the better known work.